Tantalum oxynitride thin films: Assessment of the photocatalytic efficiency and antimicrobial capacity - Cristea, Daniel (2019)
Tantalum oxynitride thin films have been deposited by reactive magnetron sputtering, using a fixed proportion reactive gas mixture (85% N2 + 15% O2). To produce the films, the partial pressure of the mixture in the working atmosphere was varied. The characteristics of the produced films were analyzed from three main perspectives and correspondent correlations: the study of the bonding states in the films, the efficiency of photo-degradation, and the antibacterial/antibiofilm capacity of the coatings against Salmonella. X-ray Photoelectron Spectroscopy results suggest that nitride and oxynitride features agree with a constant behavior relative to the tantalum chemistry. The coatings deposited with a higher reactive gas mixture partial pressure exhibit a significantly better antibiofilm capacity. Favorable antibacterial resistance was correlated with the presence of dominant oxynitride contributions. The photocatalytic ability of the deposited films was assessed by measuring the level of degradation of an aqueous solution containing methyl orange, with or without the addition of H2O2, under UV or VIS irradiation. Degradation efficiencies as high as 82% have been obtained, suggesting that tantalum oxynitride films, obtained in certain configurations, are promising materials for the photodegradation of organic pollutants (dyes).